HIF-1α restricts NF-κB-dependent gene expression to control innate immunity signals - Daniel Bandarra; John Biddlestone; Sharon Mudie; H.-Arno J. Müller; Sonia Rocha (The Company of Biologists, 2015)
Hypoxia and inflammation are intimately linked. It is known that nuclear factor κB (NF-κB) regulates the hypoxia-inducible factor (HIF) system, but little is known about how HIF regulates NF-κB. Here, we show that HIF-1α represses NF-κB-dependent gene expression. HIF-1α depletion results in increased NF-κB transcriptional activity both in mammalian cells and in the model organism Drosophila melanogaster. HIF-1α depletion enhances the NF-κB response, and this required not only the TAK-IKK complex, but also CDK6. Loss of HIF-1α results in an increased angiogenic response in mammalian cancer cells and increased mortality in Drosophila following infection. These results indicate that HIF-1α is required to restrain the NF-κB response, and thus prevents excessive and damaging pro-inflammatory responses.